Women's Health: Racial and Ethnic Health Inequities - Sarto, Gloria E. (Global Advances in Health and Medicine, 2013)
Starting in the late 1980s and throughout the 1990s, reports appeared in the literature describing the poor health status and poor health outcomes experienced by minority populations, especially blacks, in the United States. Additionally, attention was brought to the limited access to health services for minority populations. These reports prompted Congress to request the Institute of Medicine (IOM) to conduct a study to assess differences in the kinds and quality of healthcare received by US racial and ethnic minorities and nonminorities. The study culminated in the report Unequal Treatment: Confronting Racial and Ethnic Disparities in Health Care.(1) Among the recommendations included in the report published in 2003 is a need for (1) change in legal, regulatory, and policy interventions and (2) health systems interventions. The committee extended the recommendations to include (3) implementation of programs to enhance individual education and empowerment, (4) a need for research into identifying racial and ethnic disparities and the development of and assessment of intervention strategies, and (5) a need to integrate cross-cultural education into the training of all health professionals.(1) Subsequent to this report, there has been an increase in efforts to increase diversity among healthcare providers and research investigators.(2) The American Association of Medical Colleges (AAMC) continues to encourage recruitment of minorities to careers in medicine, to stress the importance of a diverse medical school faculty and administration, and to graduate culturally competent healthcare providers who will decrease health disparities and improve health equity. Additionally, as noted by Ginther et al in 2011, there continues to be a need to increase diversity at the National Institutes of Health (NIH) not only among the workforce but also among the recipients of awards.(3) To this end, the NIH has established the Working Group on Diversity in the Biomedical Research Workforce to monitor the efforts of the NIH to increase diversity and to suggest remedies.(4)